Pharmacokinetics of proguanil in malaria patients treated with proguanil plus atovaquone - M. D. Edstein (2018)
Clinical studies have shown atovaquone (ATQ), a new blood schizontocidal drug, in combination with proguanil (PROG) to be very effective in the treatment of acute multidrug-resistant falciparum malaria. The multiple dose pharmacokinetics of PROG were determined in Thai patients with acute falciparum malaria given PROG alone (200 mg PROG twice a day for 3 days, n = 4) and concurrently PROG and ATQ (200 mg PROG and 500 mg ATQ twice a day for 3 days, n = 12). There were no statistical differences (p > 0.05) in the area under the plasma drug concentration-time curve (AUC), apparent oral clearance (CL/F) and elimination half-life (t12) of PROG between patients given PROG alone and PROG/ ATQ. The median (range) kinetic values of PROG in patients given PROG alone and PROG/ATQ were respectively: CL/F = 1.25 1/h/kg (0.99-1.45) and 0.95 (0.73-1.32) 1/h/kg, and t1/2 = 14.2 hours (9.3-16.8) and 13.6 hours (9.1-17.6). The CL/F and t1/2of PROG in the Thai patients treated with the 2 treatment regimens were also comparable to values reported in healthy Thai volunteers given a standard prophylactic dose (200 mg PROG). The results of this preliminary study suggest that ATQ is unlikely to affect the pharmacokinetics of PROG to a clinically important extent at an ATQ dosage of 500 mg twice a day for 3 days in malaria infected patients.